H optimal kontrol probleminde lineer matris eşitsizlikleri yaklaşımı - Akın, Murat (Fen Bilimleri Enstitüsü, 1997)
Bu çalışmada, 9/ optimal kontrol problemi ile bu probleme getirilen ve yeni bir yaklaşım tarzı olan Lineer Matris Eşitsizlikleri üzerinde durulmuştur. %> optimal kontrol problemi 94 yaklaşımından farklı olarak görece yakın bir zamanda gelişme kaydeden bir araştırma alanıdır. Sistemlere gelen bozucu unsurları etkisizleştirme düşüncesi bozuculardan çıkışlara transfer fonksiyonları matrisinin sonsuz normunu minimum yapma düşüncesini doğurdu. Ancak 9/a> normunun 9/g normunun tersine doğrudan hesaplanması oldukça zordu. Geliştirilen iterasyon yaklaşımları gelişmiş bilgisayar ve bilgisayar programlarını zorunlu kılıyordu. Lineer matris eşitsizlikleri ise Lypunov ' un kararlılık analizinde (1890) ilk kez basit olarak ortaya çıktı ve genelde Sovyet bilimadamlarının (Lur ' e, Postnikov vb..) çalışmalarında görüldü. Bu eşitsizliklerin tıpkı 9/o> optimal kontrol problemi gibi çözümünün zor olması uzun süre önem kazanmasına engel oldu. 1988 ' de Nesterov ve Nemirovski 'nin bu eşitsizliklerin çözümünde ilerleme sağlaması, otomatik kontrol teorisi için önemli bir gelişmedir. Bu tezin inceleme alam içinde yer alan C.Scherer, P.Gahinet ve M.Chilali ' nin çalışmaları (1994-1996) kutup yerleştirme, 9/« kontrol, 94 kontrol vb., pekçok otomatik kontrol probleminin Lineer Matris Eşitsizlikleri haline dönüştürülebileceğini gösterdi. 1995 ' te P.Gahinet, A.Nemirovski, AJXaub ve M.Chilali ' nin bir araya gelerek MATLAB 4.2c.l uygulama programının içine LMI Control Toolbox 1.0 'ı eklemeleri ve yukarıdaki kontrol problemlerini ayrı ayrı veya birarada ele alıp çözmeleri gelişmelerin son aşamalarım oluşturuyor. Burada, bu programlar kullanılarak bazı kontrol problemlerinin nasıl çözüldüğü ve istenen performansları sağlayacak kontrollörlerin nasıl tasarlandığı gerekli simülasyonlar da yapılarak incelenmeye çalışılmıştır.

Introduction The popular performance measure in optimal control theory is %, norm, which is defined in the frequency-domain for a stable transfer matrix T(s) as l|T(s)

oo := sup(amax [ T( j«> )] ) (^max : maksimum singular value) Many classical control objectives such as disturbance attenuation, robust stabilization of uncertain systems can be expressed by using %, synthesis techniques. Since they involves solving two Riccati equations, %o synthesis is more complex than Linear Quadratic Gaussian (LQG) synthesis. First of all, let's consider the following basic block diagram: Here P(s) is the generalized plant and K(s) is the controller. Only finite- dimensionaL linear time-invariant (LTI) systems and controllers will be considered in this work. The generalized plant P(s) contains what is usually called the plant in a control problem plus all weighting functions. The signal w contains all external inputs, including disturbances, sensor noise and commands; the signal z is the output; y is also the measured output variables ; and u is the control input. P(s) = Pll(s) P12(S) P2l(s) P22(S) IX Since u=K(s)y, the closed-loop transfer function matrix from disturbance w to controlled output z is z = PnW + Pnu y = P21W + P22U z = Pnw + Pi2.K(s)y y = P2iW + P22.K(s)y y-P22.K(s)y = P21W [I-P22K]y=P21w y=[I-P22K]1P21.w z = Paw + P12K[I-P22K] ^Pmw z = (Pu + Pi2K[I-P22K]-1P2i).w Tw(s) = P11 + PoKCI-PiîK)-1?!!. The suboptimal ^«j control problem of parameter y consists of finding a controller K(s) such that. the closed-loop system is internally stable,. the %o norm of Tj^s) (the maximum gain from w to z) is strictly less than y. Solutions of this problem (if any) will be called y-suboptimal controllers. As usual in state-space approaches to 9fc control, some minimal realization of plant P is introduced: dx/dt= Ax+ Biw + B2u z = CiX + DnW +Dnu y = C2x + D2iW +D22u The problem dimensions are summarized by: AeST* ;l>ne9PİXmİ ;D22e9p2xm2 Throughout this thesis, the assumptions on the plant parameters are:. P(s) is a finite-dimensionaljCausal and linear time-invariant (LTI) system,. (A,B2»C2) is stabilizable and detectable,. D22=0. Under these assumptions, find any proper real-rational controller K(s) given by dxk/dt=AKxk+BKy u= CKxk+ÜKy or kxk K(s)=Dk+Ck(sI-Ak)-1Bk, AKe$ and a (not necessarily minimal) realization of the closed-loop transfer function from w to z is obtained as dx/dt=Ax+Biw+B2U=Ax+B1w+B2CKXk+B2DKy 2=Cıx+D11w+Dı2u=CıX+Dııw+Di2CKXk+Di2DKy y=C2x+D2iw dx/dt=Ax+B1w+B2CKXk+B2DKC2x+B2DKD21w dxk/dt= AKXk+BKC2X+BKD2iw z=C1x+D11w+D12CKXk+D12DKC2X+Di2DKD2iW TUs)=Dd+ CdCsI-Acij'Bc Ae,= rA + B2DKC2 B2CK"1 Bcl= Tb! + B2DKD21 L BKC2 AkJ I BKD21 J Cd = rCi+DiaDKC2"| Dd= Dn+D12DKD21 :d=rc,+D12DKC2"| I D12CK For more details in these relationships, see GAHINET and APKARIAN (1994). We first recall the Bounded Real Lemma for continuous-time systems. This lemma helps turning the %, suboptimal constraints into a matrix inequality. 2) Solvability of continuous-time control problems Lemma 2.1 Consider a continous-time transfer function T(s) of (not necessarily rninimal) realization T(s) = D + C(sI-A)"xB. The following statements are equivalent: 1. II T(s) D» < y and A is stable. (Re(Xi(A) < 0 ) 2. There exists a symmetric positive definite solution X to the LMI: XI < 0 (2.1) Proof: See SCHERER (1990). 3) Linear Matrix Inequalities Definition (3.1) cD = {ze C: fi)(z)<0} and f
A survey on 9k design with pole placement constraints : an LMI approach
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1997
Keywords: Denetim sistemleri; Doğrusal matris eşitsizlikleri; Control systems; Linear matrix inequalities